Sociology and the mirror of nature: Robert Brandom and the strong programme. (March 2017) - Law, Duncan; Pepperell, Nicole
The 'strong programme' in the sociology of scientific knowledge has both exerted enormous influence on science studies, and been widely criticised for its apparent commitment to epistemological relativism. In this article we argue that the recent work of the pragmatist philosopher Robert Brandom provides a potential resolution to these debates. Brandom's work, we argue, meets the key commitments of the strong programme, including particularly commitments to symmetry and reflexivity, while also demonstrating how these commitments are compatible with a robust – but non-dogmatic, pragmatist – concept of objective knowledge. In so doing, it provides a theoretically developed account of why the traditions of empirical science studies that emerged from the strong programme need not be seen as undermining scientific objectivity, while it also supports a reflexive, critical sociological analysis of scientific practice.